Molecular Fingerprints of Borderline Changes in Kidney Allografts Are Influenced by Donor Category - Hruba, Petra; Krejcik, Zdenek; Dostalova Merkerova, Michaela; Klema, Jiri; Stranecky, Viktor; Slatinska, Janka; Maluskova, Jana; Honsova, Eva; Viklicky, Ondrej (Frontiers in Immunology, 2020)
The fate of transplanted kidneys is substantially influenced by graft quality, with transplantation of kidneys from elderly and expanded criteria donors (ECD) associated with higher occurrence of delayed graft function, rejection, and inferior long-term outcomes. However, little is known about early molecular fingerprints of these events in different donor categories. Borderline changes represent the most frequent histological finding early after kidney transplantation. Therefore, we examined outcomes and transcriptomic profiles of early-case biopsies diagnosed as borderline changes in different donor categories. In this single-centre, retrospective, observational study, we compared mid-term outcomes of kidney transplant recipients with early borderline changes as a first pathology between ECD (n=109), standard criteria donors (SCD, n=109), and living donor (LD, n=51) cohorts. Intragraft gene expression profiling by microarray was performed in part of these ECD, SCD and LD cohorts. Although five-year graft survival in patients with borderline changes in early-case biopsies was not influenced by donor category (log rank p=0.293), impaired kidney graft function (eGFR by CKD-EPI) at M3, 1, 2, and 3 years was observed in the ECD cohort (p<0.001). Graft biopsies from ECD donors had higher vascular intimal fibrosis and arteriolar hyalinosis compared to SCD and LD (p<0.001), suggesting chronic vascular changes. Increased transcripts typical for ECD, as compared to both LD and SCD, showed enrichment of the inflammatory, defence and wounding responses and the ECM-receptor interaction pathway. Additionally, increased transcripts in ECD vs. LD showed activation of complement and coagulation and cytokine-cytokine receptor pathways along with platelet activation and cell cycle regulation. Comparative gene expression overlaps of ECD, SCD, and LD using Venn diagrams found 64 up- and 16 down-regulated genes in ECD compared to both LD and SCD. Shared increased transcripts in ECD vs. both SCD and LD included thrombospondin-2 (THBS2), angiopoietin-like 4 (ANGPTL4), collagens (COL6A3, COL1A1), chemokine CCL13 and interleukin IL11 and most significantly, downregulated transcripts included proline-rich 35 (PRR35) and fibroblast growth factor 9 (FGF9). Early borderline changes in ECD kidney transplantation are characterized by increased regulation of inflammation, extracellular matrix remodelling and acute kidney injury transcripts in comparison with both LD and SCD grafts.